Інформаційна влада публічної адміністрації: вплив глобальних тенденцій - Antoshina, Iryna; Антошина, І. В. (Одеса : Видавничий дім «Гельветика», 2019)
The comprehensive informatization of a society, the widespread introduction of new information technologies updated the discussions about the information power as a function of public administration in its broadest understanding. In modern conditions the information power plays the defining role in the life of a society and globalization processes. Indeed, the globalization itself is the result of the exchange of an information, the implementation of an information influence on public institutions in the most modern states. Most politically-legal institutes, the political relations, the forms of political and information impact on the public relations and public consciousness change due to the influence of the information power. In general, the information power has the wide impact on the formation of behavior of a personality and a society. The forming of the information power directly bind with formation of an information society, in which information becomes the main economic resource, and the information sector comes out on the top on rate of growth in today’s globalized world. The intellectual property becomes the main form of ownership, a human capital becomes the important; an information becomes a subject of mass consumption, the new legal bases of functioning of an information society are formed. Now, freedom of speech and information on the basis of the rule of law and the respect of human rights are the main postulates of the creation of a civil society, the statement of a real democracy. Therefore, the limits of the existence of the information power have to be agreed with the rights and the freedoms of a person. So, the right for access to information becomes one of inalienable rights of a human and a citizen. A priority task of the Ukrainian state is the ensuring the freedom of speech, the freedom of an information, the right for expression of opinion and the citizen`s position, the right for the receipt and the dissemination of the reliable information without obstacles. Всеосяжна інформатизація суспільства, широке впровадження нових інформаційних технологій значно актуалізували дискусії про інформаційну владу як функцію публічної адміністрації у найбільш широкому її розумінні. У сучасних умовах інформаційна влада відіграє визначальну роль у житті суспільства та глобалізаційних процесах. Власне і сама глобалізація відбувається завдяки обміну інформацією, здійсненню інформаційного впливу на суспільні інститути у більшості сучасних держав. Завдяки впливу інформаційної влади змінюються більшість політико-правових інститутів, політичні відносини, форми політичного та інформаційного впливу на суспільні відносини і суспільну свідомість. Інформаційна влада чинить широкий вплив на формування поведінки особистості і суспільства в цілому. Формування інформаційної влади безпосередньо пов’язане зі становленням інформаційного суспільства, в якому інформація стає головним економічним ресурсом, а інформаційний сектор виходить на перше місце за темпами зростання у сучасному глобалізованому світі. Основною формою власності стає інтелектуальна власність, важливого значення набуває людський капітал; інформація стає предметом масового споживання, формуються нові правові засади функціонування інформаційного суспільства. На теперішній час свобода слова та інформації на основі верховенства права і поваги прав людини є основними постулатами побудов громадянського суспільства, утвердження справжньої демократії. Тому межі існування інформаційної влади повинні бути узгоджені з правами і свободами людини. Так, право на доступ до інформації стає одним з невід’ємних прав людини і громадянина. Пріоритетним завданням української держави є забезпечення свободи слова, свободи інформації, право на вираження думки і позиції громадянина, право на отримання і поширення достовірної інформації без перешкод.
Public administration information power: the impact of global trends
Антошина І. В. Інформаційна влада публічної адміністрації: вплив глобальних тенденцій / І. В. Антошина // Lex Portus : юрид. наук. журн. / редкол. : С. В. Ківалов (голов. ред. ради), Б. А. Кормич (голов. ред.), Т. В. Аверочкіна (наук. ред., відп. секр.) [та ін.] ; НУ "ОЮА", ГО "МА Святий Миколай". - Одеса : Видавничий дім «Гельветика», 2019. - № 5. – C. 77-92
Keywords: information society; information space; information power; state power; public administration; power resources; globalization; інформаційне суспільство; інформаційна влада; державна влада; публічне адміністрування; глобалізація; информационное общество; информационная власть; публичное администрирование; ресурсы власти; глобализация; государственная власть